IMPACT OF FOOD HABITS ON HEALTH: ANALYTICAL STUDY WITH SPECIAL REFERENCE TO TRIBAL WOMEN - Sinha, Kanchanmala; Kumari, Seema (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study analyses the food habits of tribal women and the impact of their diet on their health. The study followed various research methods such as survey, interview, diet analysis, and health data collection. The survey elicited information on food patterns, likes-dislikes and dietary changes of tribal women, while the interview analysed their nutritional status and diet-related problems in depth. Diet analysis assessed the nutritional quality of the daily diet of women, which revealed nutritional deficiencies in their diet and the need for improvement. Health data collection collected information on health problems of tribal women such as malnutrition, iron deficiency and underweight. The study found that tribal women lack diversity in their diets, which negatively impacts their nutritional status and health.